2007
DOI: 10.1038/ni1474
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive epigenetic profiling identifies multiple distal regulatory elements directing transcription of the gene encoding interferon-γ

Abstract: Unlike the well defined T helper type 2 cytokine locus, little is known about the regulatory elements that govern the expression of Ifng, which encodes the 'signature' T helper type 1 cytokine interferon-gamma. Here our evolutionary analysis showed that the mouse Ifng locus diverged from the ancestral locus as a result of structural rearrangements producing deletion of the neighboring gene encoding interleukin 26 and disrupting synteny 57 kilobases upstream of Ifng. Proximal to that disruption, we identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
306
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(334 citation statements)
references
References 50 publications
20
306
2
2
Order By: Relevance
“…IL-22 is a member of the IL-10 family of cytokines, which also includes IL-10, IL-19,IL-20, IL-24, IL-28a, and IL-28b as well as IL-26 and IL-29, two IL-10 family members that are only expressed in humans [100][101][102][103]. Whereas the Il29 gene exists in mice, but is nonfunctional due to the existence of a stop codon within the first exon [104,105], the Il26 gene is disrupted in rodents [106]. The unique IL-22R is a heterodimeric transmembrane receptor complex consisting of IL-22R1 and IL-10R2.…”
Section: Il-22mentioning
confidence: 99%
“…IL-22 is a member of the IL-10 family of cytokines, which also includes IL-10, IL-19,IL-20, IL-24, IL-28a, and IL-28b as well as IL-26 and IL-29, two IL-10 family members that are only expressed in humans [100][101][102][103]. Whereas the Il29 gene exists in mice, but is nonfunctional due to the existence of a stop codon within the first exon [104,105], the Il26 gene is disrupted in rodents [106]. The unique IL-22R is a heterodimeric transmembrane receptor complex consisting of IL-22R1 and IL-10R2.…”
Section: Il-22mentioning
confidence: 99%
“…1). Also conserved were the chromosomal arrangement and transcription orientation of these genes except that in mouse the IL-22 gene was duplicated and the IL-26 gene was an untranscribed pseudogene which was disrupted by the insertion of a long interspersed nuclear element (LINE) and insertion of a long terminal repeat (LTR)-LINE-LTR (Schoenborn et al 2007). Notably, a gene encoding an IFN-γ-related protein (IFN-γrel) located at upstream of fish IFN-γ gene was not present in Xenopus, suggesting that the IFN-γrel gene is uniquely confined to teleosts (Igawa et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In more distal locations, enhancer elements are found in the conserved noncoding sequences (CNS) 3 (10 -14). Some of the CNS have also been shown to have boundary function (11). In 3C analyses, dynamic and distinct interactions between different DNA segments of the IFN-␥ locus were found in differentiating Th1 and Th2 cells (15).…”
Section: Temporal and Spatial Changes Of Histone 3 K4 Dimethylation Amentioning
confidence: 99%
“…Previous works have documented several types of histone modifications at the IFN-␥ gene during Th1 and Th2 cell differentiation (11, 12, 19 -26). Importantly, the study by Schoenborn et al (11) identified elevated levels of the active modification histone H3 lysine 4 (H3K4) methylation at CNS sites distributed over 100 kb of the IFN-␥ locus in Th1 cells. In contrast, Th2 cells acquired the repressive modification histone H3 lysine 27 (H3K27) methylation at the IFN-␥ locus (11,25).…”
Section: Temporal and Spatial Changes Of Histone 3 K4 Dimethylation Amentioning
confidence: 99%
See 1 more Smart Citation